The Effect Seizure Focus on Regional Language Processing Areas - Duke, Elizabeth S (2012)
PURPOSE: To determine the effect of seizure focus location within the left hemisphere on the expression of regional language dominance. METHODS: In this cross sectional study we investigated 90 patients (mean age 23.3±12.9 years) with left hemisphere focal epilepsy (mean age onset 11.7 ±8.3 years). 18 patients had a frontal lobe focus, 72 temporal lobe focus (43 mesial; 29 neocortical). Subjects performed an auditory word definition language paradigm using 3T BOLD EPI fMRI. Data was analyzed in SPM2. Regional laterality indices (LI) for inferior frontal gyrus (IFG), and Wernicke’s area (WA), were calculated using a bootstrap method. Categorical language dominance and mean LI were analyzed. KEY FINDINGS: Mean WA LI was lower for subjects with a mesial temporal focus compared to a frontal focus (p=0.04). There was a greater proportion of atypical language in WA for subjects with a mesial temporal focus compared to a frontal focus (χ(2)=4.37, p=0.04). WA LI did not differ for subjects with a neocortical focus compared to a mesial focus or a frontal focus. Mean IFG LI and proportion of atypical language in IFG were similar across seizure focus groups. Age and age of onset were not correlated with mean laterality in WA or IFG. Epilepsy duration tended to be negatively correlated with WA LI (r=−0.18, p=0.10), but not IFG LI. SIGNIFICANCE: Temporal lobe foci have wide-ranging effects on the distributed language system. In contrast, the effects of a frontal lobe focus appear restricted to anterior rather than posterior language processing areas.